2006
DOI: 10.1089/neu.2006.23.1125
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reinnervation of the Canine Bladder after Spinal Root Transection and Immediate End-on-End Repair

Abstract: The goal of this study was to transect and immediately repair ventral roots, selected by their ability to stimulate bladder contraction, to assess the feasibility of bladder reinnervation in a canine model. Brain-derived neurotrophic factor (BDNF) was delivered via an osmotic pump (0.5 or 5 mg/mL) to a cuff surrounding the reanastomosis site to the two root bundles on one side. Electrodes were implanted bilaterally immediately proximal to the site of surgical reanastomosis. Results were compared to four root-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 28 publications
7
69
0
Order By: Relevance
“…Since we cut the S1 and S2 roots, any anomalous S3 innervation to the bladder would have been spared. In our pervious reports (Ruggieri et al, 2008;Ruggieri et al, 2006) and in this current report, only two nerve roots on each side of the spinal cord (S1 and S2) were found to induce bladder contractions during electrical stimulation in all dogs studied. However, it is possible that a very few number of motor fibers innervate the bladder in some animals through S3 roots; however, these were apparently below the level needed to induce bladder pressure increases during conus medullaris stimulation.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Since we cut the S1 and S2 roots, any anomalous S3 innervation to the bladder would have been spared. In our pervious reports (Ruggieri et al, 2008;Ruggieri et al, 2006) and in this current report, only two nerve roots on each side of the spinal cord (S1 and S2) were found to induce bladder contractions during electrical stimulation in all dogs studied. However, it is possible that a very few number of motor fibers innervate the bladder in some animals through S3 roots; however, these were apparently below the level needed to induce bladder pressure increases during conus medullaris stimulation.…”
Section: Discussionsupporting
confidence: 55%
“…Using a canine model, we have previously shown that the urinary bladder can become reinnervated following sacral nerve root transection and immediate end-on-end repair based on increased bladder pressure upon FES and neurotracing studies using fluorescent and lipophilic dyes (Ruggieri et al, 2006). Similar nerve transection and immediate end-to-end suturing studies in pigs has demonstrated return of the micturition reflex in two animals at 14 and 20 weeks postoperatively (Conzen and Sollmann, 1982).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Schwann cells derived from motor-specific axons (ie, ventral roots) appear to be better suited for sustaining motor axon elongation compared with those originating in the more traditional donor nerves (eg, sural) (82). In the dog, studies of bladder reinnervation after nerve root transection and repair using some of these newer strategies are promising (83,84). Finally, clinical trials of peripheral nerve repair with synthetic GC are under way, with encouraging results, provided that repair distances are short and resorbable GC are used (33).…”
Section: Discussionmentioning
confidence: 99%